Verb second grammar internal and grammar external interfaces - Lohnstein, Horst; Tsiknakis, Antonios (Interface explorations ;, 2020)
This book addresses a general phenomenon in the European languages: verb second. The articles provide a comprehensive survey of synchronic vs. diachronic developments in the Germanic and Romance languages.0New theoretical insights into the interaction of the properties of verbal mood and syntactic structure building lead to hypotheses about the mutual influence of these systems. The diachronic change in the syntax together with changes in the inflectional system show the interdependence between the syntactic and the inflectional component.0The fact that the subjunctive can license verb second in dependent clauses reveals further dependencies between these subsystems of grammar. "Fronting finiteness" furthermore constitutes an instance of a main clause phenomenon. Whether "assertion" or "at-issueness" are encoded through this grammatical process will be a matter in the debates discussed in the book. Moreover, information structure appears to be directly related to the fronting of other constituents in front of the finite verb. Questions concerning the interrelations between these various subcomponents of the grammatical system are investigated.